1992
DOI: 10.1111/j.1365-2249.1992.tb03039.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti-mitochondrial antibody IgG subclass distribution and affinity in primary biliary cirrhosis

Abstract: SUMMARYWe have studied the total IgG subclass and anti-mitochondrial antibody (AMA) specific IgG subclass distribution in primary biliary cirrhosis (PBC) sera. In order to solve the problems caused by thc differing affinities of subclass specific monoclonals and the competitive inhibition of antibodies in a whole serum assay. si.\ sera were separated into su be I ass-specific fractions by affinity-depletion chromatography. AMA subclass distribution of 20 further sera from patients with PBC was assessed using c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Previous studies observed that IgG3-AMA were predominant in IIF-AMA-positive PBC sera, [7][8][9][10][11] possibly as a result of the exclusion of IIF-AMA-negative sera. Indeed, the inclusion of a relatively large number of seronegative sera at IIF allowed us to obtain different data, which might also suggest a serological uniqueness of Japanese PBC cases.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Previous studies observed that IgG3-AMA were predominant in IIF-AMA-positive PBC sera, [7][8][9][10][11] possibly as a result of the exclusion of IIF-AMA-negative sera. Indeed, the inclusion of a relatively large number of seronegative sera at IIF allowed us to obtain different data, which might also suggest a serological uniqueness of Japanese PBC cases.…”
Section: Discussionmentioning
confidence: 91%
“…5 All three major Ig classes are found among AMA, with a predominance of IgG and IgM, 6 and several studies have suggested that IgG2 and IgG3 subclasses are predominant in IIF-AMA-positive PBC sera. [7][8][9][10][11] Interestingly, this is in contrast with the common subclass distribution in adult sera where IgG1 account for approximately 66% of IgG. 12 Under normal conditions, IgG subclasses are determined by the target antigen characteristics and the cytokine environment around B cells, with IgG2 predominating in response to polysaccharide antigens 13 and IgG3 to proteins.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…and 3/17 cases of FLT. This antibody is shared with other autoimmune conditions specifically primary biliary cirrhosis (30,31) and the two conditions are known to coexist (32,33) .Antinuclear antibody, was positive in 2/4 cases of H.T. and 1/17 cases of FLT which was of grade II.…”
Section: Antibodies In Thyroiditismentioning
confidence: 91%
“…There is no polyelonal B cell activation in anti-GBM disease [12], and the only other autoantibodies known to be found in a significant proportion of cases are anti-neutrophil cytoplasm antibodies (ANCA) [ 13]. We were therefore surprised to observe signifieant binding to PDH in a number of anti-GBM sera used as controls in an ELISA that we developed for AMA [14]. The series of experiments reported in this study were designed to assess the extent and specificity of this phenomenon.…”
Section: Introductionmentioning
confidence: 99%